State-dependent or time-dependent pricing? New evidence from a monthly firm-level survey: 1980-2017 - Huw Dixon; Christian Grimme (Cardiff University, Cardiff Business School, 2021)
We examine the relative importance of time and state dependence in the price-setting decisions of firms using a monthly panel of German firms over the period 1980-2017. We propose a refined version of time dependence by introducing different hazard functions for price increases and decreases. We find three sets of results. First, time dependence is much more important for price setting than what the previous literature has found. Second, price decreases can be well explained by time dependence alone. Price increases are best predicted by the interaction of time-dependent and firm-specific state factors. Third, time dependence for price increases and decreases look completely different from each other. Our empirical results suggest that theoretical models should integrate both time and state dependence rather than developing the approaches separately.
Keywords: E30; E31; E32; 330; Survey Data; Price Setting; Extensive Margin; State-Dependent Pricing; Time-Dependent Pricing